'The Brick' is not a brick: a comprehensive study of the structure and dynamics of the central molecular zone cloud G0.253+0.016. Issue 2 (17th February 2019) - Henshaw, J D; Ginsburg, A; Haworth, T J; Longmore, S N; Kruijssen, J M D; Mills, E A C; Sokolov, V; Walker, D L; Barnes, A T; Contreras, Y; Bally, J; Battersby, C; et al.
Abstract: In this paper we provide a comprehensive description of the internal dynamics of G0.253+0.016 (a.k.a. 'the Brick'); one of the most massive and dense molecular clouds in the Galaxy to lack signatures of widespread star formation. As a potential host to a future generation of high-mass stars, understanding largely quiescent molecular clouds like G0.253+0.016 is of critical importance. In this paper, we reanalyse Atacama Large Millimeter Array cycle 0 HNCO J  = 4(0, 4) − 3(0, 3) data at 3 mm, using two new pieces of software that we make available to the community. First, scousepy, a Python implementation of the spectral line fitting algorithm scouse . Secondly, acorns (Agglomerative Clustering for ORganising Nested Structures), a hierarchical n -dimensional clustering algorithm designed for use with discrete spectroscopic data. Together, these tools provide an unbiased measurement of the line-of-sight velocity dispersion in this cloud, $\sigma _{v_{\mathrm{ los}}, {\rm 1D}}=4.4\pm 2.1$ km s −1, which is somewhat larger than predicted by velocity dispersion-size relations for the central molecular zone (CMZ). The dispersion of centroid velocities in the plane of the sky are comparable, yielding $\sigma _{v_{\mathrm{ los}}, {\rm 1D}}/\sigma _{v_{\mathrm{ pos}}, {\rm 1D}}\sim 1.2\pm 0.3$ . This isotropy may indicate that the line-of-sight extent of the cloud is approximately equivalent to that in the plane of the sky. Combining our kinematic decomposition with radiative transfer modelling, we conclude that G0.253+0.016 is not a single, coherent, and centrally condensed molecular cloud; 'the Brick' is not a brick . Instead, G0.253+0.016 is a dynamically complex and hierarchically structured molecular cloud whose morphology is consistent with the influence of the orbital dynamics and shear in the CMZ.